Clinical Validation of a Protein Biomarker Panel for Non-Small Cell Lung Cancer - Jung, Young Ju; Oh, In-Jae; Kim, Youndong; Jung, Jong Ha; Seok, Minkyoung; Lee, Woochang; Park, Cheol Kyu; Lim, Jung-Hwan; Kim, Young-Chul; Kim, Woo-Sung; Choi, Chang-Min (Journal of Korean medical science, 2018)
We validated the diagnostic performance of a previously developed blood-based 7-protein biomarker panel, AptoDetect™-Lung (Aptamer Sciences Inc., Pohang, Korea) using modified aptamer-based proteomic technology for lung cancer detection. Non-small cell lung cancer (NSCLC), 200 patients and benign nodule controls, 200 participants were enrolled. In a high-risk population corresponding to ≥ 55 years of age and ≥ 30 pack-years, the diagnostic performance was improved, showing 73.3% sensitivity and 90.5% specificity with an area under the curve of 0.88. AptoDetect™-Lung (Aptamer Sciences Inc.) offers the best validated performance to discriminate NSCLC from benign nodule controls in a high-risk population and could play a complementary role in lung cancer screening.